Analysis of deformability modulus by linear and nonlinear elastic methods in ceramic structural masonry and mortars - N. A. Cerqueira; M. T. Marvila; A. R. G. de Azevedo; J. Alexandre; G. C. Xavier; V. B. de Souza (Cerâmica, 2020)
Abstract There are studies analyzing the parameters of structural masonry strength, however few are performed evaluating the interference of the mortar in the deformability parameters. The objective of this study was to verify the theories of elasticity (Hooke’s linear model and nonlinear models by Ghosh, Duffing, and Martin, Roth, and Stiehler) applied to structural masonry. Ceramic blocks were pressed and fired at 890 ºC and mortars prepared with the proportion 1:1:5:0.5:2 of cement: hydrated lime: sand: PVA binder: water. The materials were tested in compression individually and in prisms with and without the use of mortars. The results obtained with the linear elastic analysis were incoherent since the deformability modulus obtained for the mortar prisms was higher than those without mortar. Performing the analysis by nonlinear theories, it was found that the results obtained were more coherent, mainly by Duffing’s theory that uses one parameter for stiffness and another for damping of the material.